A emperor between the sword and the quill: two aspects of Julian Caesar in Gaul (355-360) - Gabbardo, Gabriel Requia (Romanitas - Revista de Estudos Grecolatinos, 2026)
Much of the reputation of the Roman emperor Julian, known as “the Apostate” (355–363), as a good ruler derives from his competence as a military commander. During his tenure as Caesar in Gaul (355–360), he effectively contained the invasions of the Alamanni. His success is commonly attributed to his military skills. This article argues that Julian’s achievements also owed much to two other factors: his military perambulation through Gallic territories, which attracted the attention and approval of his subjects; and the publication of a short work on the Battle of Argentoratum, his greatest military triumph.